Marine Pelagic Ecosystem Responses to Climate Variability and Change. (16th August 2022) - Ducklow, Hugh; Cimino, Megan; Dunton, Kenneth H; Fraser, William R; Hopcroft, Russell R; Ji, Rubao; Miller, Arthur J; Ohman, Mark D; Sosik, Heidi M
Abstract: The marine coastal region makes up just 10% of the total area of the global ocean but contributes nearly 20% of its total primary production and over 80% of fisheries landings. Unicellular phytoplankton dominate primary production. Climate variability has had impacts on various marine ecosystems, but most sites are just approaching the age at which ecological responses to longer term, unidirectional climate trends might be distinguished. All five marine pelagic sites in the US Long Term Ecological Research (LTER) network are experiencing warming trends in surface air temperature. The marine physical system is responding at all sites with increasing mixed layer temperatures and decreasing depth and with declining sea ice cover at the two polar sites. Their ecological responses are more varied. Some sites show multiple population or ecosystem changes, whereas, at others, changes have not been detected, either because more time is needed or because they are not being measured.